Challenge and relief: A Foucauldian disciplinary analysis of retirement from professional association football in the United Kingdom. (December 2017) - Jones, Luke; Denison, Jim
The aim of this study was to consider the retirement experiences of British male professional association footballers by utilising Foucault's analysis of discipline discussed in Discipline and Punish: The Birth of the Prison . Specifically, we drew upon Foucault to consider how, through the various techniques and instruments of discipline, the professional football context produces 'docile footballing bodies' and how this might influence a player's experiences in retirement. We gathered our empirical material using a Foucauldian-informed interview framework with 25 former professional male football players between the ages of 21 and 34. Our analysis suggested that retirement from football was both a challenge and a relief for our participants, and that their extended period of time within football's strong disciplinary apparatus significantly influenced how they experienced their retirement.